2014
DOI: 10.1021/ol503161g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on Iodine(III) Promoted Metal-Free Dual C–H Activation Involved in the Formation of a Spirocyclic Bis-oxindole

Abstract: The mechanism of a metal-free, phenyliodine(III) bis(trifluoroacetate) promoted, dual aryl C-H activation of an anilide to a spirocyclic bis-oxindole is examined using density functional theory (M06-2X). The most preferred pathway proceeds through the involvement of a novel iodonium ion intermediate and a pivotal trifluoroacetate counterion. The two sequential aryl C-H activations, assisted by trifluoroacetate as well as the superior leaving group ability of PhI, facilitate the formation of spirocyclic bis-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…This functional group displays ahigh degree of chemoselectivity,a sd emonstrated, for example, by an octapeptide derived from Sandostatin, [18,19] or by co-enzymeA. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This functional group displays ahigh degree of chemoselectivity,a sd emonstrated, for example, by an octapeptide derived from Sandostatin, [18,19] or by co-enzymeA. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Although the chemistry of iodanes is well established,o nly recent computational studies revealed the mechanistic versatility of l 3 -iodanes, reminiscent of that of transition metals. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles. [24,25,30] Thus, the activation of reagent 1 by protonation is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sunoj and Sreenithya [ 92 ] developed a metal-free approach for the synthesis of 1,1'-dimethyl-3,3'-spirobi[indoline]-2,2'-dione ( 61 ) from N 1 , N 3 -dimethyl- N 1 , N 3 -diphenylmalonamide ( 60 ) using PIFA ( 31 ) in trifluoroethanol at room temperature. The spirolactam 61 was isolated in 75% yield ( Scheme 21 ).…”
Section: Reviewmentioning
confidence: 99%
“…In a recent report, Sreenithya and Sunoj reported a detailed mechanistic study of phenyliodonium bis‐trifluoroacetate (PIFA) promoted dual CH functionalization of an anilide derivative to form spiro bis‐oxindole framework (Scheme (a)) using DFT computations at the SMD (TFE) /M06‐2X/LANL2DZ(I),6‐31G** level of theory to shed light on the key intermediates and TSs involved . Reaction starts with initial substrate coordination to iodine(III) center through ligand exchange ( TS ( 1 a –2 a )) followed by a proton abstraction by trifluroacetate ( TS ( 2 a –3 a )) to form an iodoenolate 3 a .…”
Section: Ch Functionalizationmentioning
confidence: 99%